Influence of Potentially Remineralizing Agents on Bleached Enamel Microhardness - Borges, Alessandra Buhler [UNESP]; Samezima, L. Y. [UNESP]; Fonseca, L. P. [UNESP]; Yui, K. C. K. [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Torres, C. R. G. [UNESP] (Operative Dentistry Inc, 2009)
This study investigated the effect of the addition of calcium and fluoride into a 35% hydrogen peroxide gel on enamel surface and subsurface microhardness. Twenty extracted human third molars were sectioned to obtain enamel fragments and they were divided into four groups (n=20) according to the bleaching treatment. Group 1 received no bleaching procedure (control). Group 2 was treated with a 35% hydrogen peroxide gel (Total Bleach), Groups 3 and 4 were bleached with Total Bleach modified by the addition of sodium fluoride and calcium chloride, respectively. The microhardness of the enamel surface was assessed using a Vickers microdurometer immediately after the bleaching treatment. The specimens were sectioned in the central portion, polished and evaluated to determine the microhardness of the enamel subsurface to a depth of 125 mu m, with an interval of 25 mu m between measures. There were significant differences among the groups. In terms of surface microhardness, the bleached group exhibited the lowest means, and the calcium-modified bleached group exhibited the highest means. Regarding subsurface microhardness, there were no significant differences among the groups for the depth and interaction factors. The bleached group exhibited the lowest means, and the calcium-modified bleached group presented the highest means. It was concluded that the bleaching treatment with 35% hydrogen peroxide significantly reduced the surface and subsurface microhardness of the enamel, and the addition of fluoride and calcium in the bleaching agent increased the microhardness means of the bleached enamel.